Lippincott's textbook for nursing assistants : a humanistic approach to caregiving - Carter, Pamela J. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
Product Description: This textbook for nursing assistants will prepare students not only to function in the traditional nursing assistant role in nursing homes, hospitals, and home health, but also will prepare students to advance their careers. A nursing assistant student who uses this text will have a firm foundation by which to transition to an LPN and ultimately an RN role. The text offers a compelling art program, a direct, conversational writing style, and an emphasis on professionalism and humanism. A back-of-book CD-ROM includes an audio glossary